PowerPoint 2019 for dummies - Lowe, Doug, 1959- (Hoboken, NJ : John Wiley & Sons, Inc., 2018)
PowerPoint continues to be the go-to tool for business presentations. The software helps anyone who needs to communicate clearly by creating powerful and effective slideshow presentations featuring data in the form of charts, clip art, sound, and video. You can even use it to create presentations for the Web.
Getting started with PowerPoint 2019. Welcome to PowerPoint 2019 ; Editing slides ; Working in Outline view ; Proofing your presentations ; Don't forget your notes! ; Show time! -- Creating great-looking slides. All about fonts and text formatting ; Designing your slides ; Animating your slides ; Masters of the universe meet the templates of doom -- Embellishing your slides. Inserting pictures ; Drawing on your slides ; Charting for fun and profit ; Working with SmartArt ; Lights! Camera! Action! (adding sound and video) ; More things to insert on your slides -- Working with others. Collaborating in the cloud ; Using a slide library and other ways to reuse slides ; Exporting your presentation to other formats -- The part of tens. Ten PowerPoint commandments ; Ten tips for creating readable slides ; Ten ways to keep your audience awake.
Includes index.
Keywords: Microsoft PowerPoint (Computer file).; Presentation graphics software